Regulation of trehalose metabolism in insects: from genes to the metabolite window - Tellis, Meenakshi B.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Glycobiology, 2023)
Trehalose is a major circulatory sugar in the haemolymph of insects. It provides instant energy and protection against stress. Trehalose metabolism is associated with insect growth and development. The architecture and spatio-temporal expression dynamics of trehalose metabolism and transport genes are key for regulation. These genes are controlled by various transcription factors, largely linked to nutrition, insect development, and metamorphosis. Also, trehalose levels are affected by substrate affinities and modifications of enzymes involved in the pathway. A feedback mechanism involving the precursors and products can regulate trehalose metabolism. Further, the neuroendocrine system controls trehalose levels under normal and stressed conditions by producing different hormones. Hypotrehalosemic hormones work under surplus energy conditions to activate haemolymph trehalose uptake and degradation. In contrast, hypertrehalosemic hormones stimulate trehalose production in the fat body and its transport to the haemolymph. However, trehalose metabolism regulation in insects needs to be studied in detail. This review discusses aspects of trehalose synthesis, transport, and degradation dynamics in developmental transition and stress response. Unraveling the epigenetic factors, transcriptional control and chemical or genetic modulators can provide further insights into the intricate regulation of trehalose in a development- and tissue-specific manner. This molecular information about effectors and regulators of trehalose metabolism can be applied in developing diverse biotechnological applications.
Keywords: Hormone; Insect development; Metabolic regulation; Stress; trehalose